MUC1 Oncoprotein Regulates Bcr-Abl Stability and Pathogenesis in Chronic Myelogenous Leukemia Cells - Kawano, Takeshi (2007)
Chronic myelogenous leukemia (CML) results from expression of the Bcr-Abl fusion protein in hematopoietic stem cells. The MUC1 heterodimeric protein is aberrantly overexpressed in diverse human carcinomas. The present studies show that MUC1 is expressed in the human K562 and KU812 CML cell lines. The results show that MUC1 associates with Bcr-Abl through a direct interaction between the Bcr N-terminal region and the MUC1 cytoplasmic domain. Stable silencing of MUC1 decreased cytoplasmic Bcr-Abl levels by promoting Bcr-Abl degradation. Silencing MUC1 was also associated with decreases in K562 and KU812 cell self-renewal capacity and with a more differentiated erythroid phenotype. The results further show that silencing MUC1 increases sensitivity of CML cells to imatinib-induced apoptosis. Analysis of primary CML blasts confirmed that, as found with the CML cell lines, MUC1 blocks differentiation and the apoptotic response to imatinib treatment. These findings indicate that MUC1 stabilizes Bcr-Abl and contributes to the pathogenesis of CML cells by promoting self renewal and inhibiting differentiation and apoptosis.